NETFLIX'S MARKETING COMMUNICATION STRATEGY TO PROMOTE SQUID GAME SEASON 2 - Silalahi, Putri Esaskia; Sumanti, Solihah Titin (International Journal of Cultural and Social Science, 2025)
The development of digital technology drives major changes in movie industry promotion, including in promotion and marketing patterns. Facing intense competition from other platforms, Netflix needs to integrate various communication channels to retain and attract customers, especially in promoting Squid Game Season 2. The problem in this research is how Netflix uses elements of marketing communication strategy in the process of promoting the Squid Game Season 2 series. This study aims to identify the marketing communication strategies used by Netflix in promoting the Squid Game Season 2 series.The method used in this research is a qualitative approach with a descriptive method. Data collection techniques include non-participatory observation, documentation, and literature study. The data were analyzed using the Integrated Marketing Communication (IMC) theory. The results show that Netflix implemented marketing communication strategies through four elements: advertising via social media in the form of posters, teasers, trailers, cast reaction content, and the use of original soundtracks; sales promotion through collaborations with various well-known brands, the opening of pop-up stores, and the distribution of free merchandise; public relations through press conferences, exclusive interviews, and the organization of global events; and personal selling through meet and greet events between the cast and fans.